The Problems of Learning Islamic Religious Education at Kasui 1 State High School Way Kanan Regency - Salamayanti, Salamayanti; Syafe'I, Imam; Akmansyah, Muhammad (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This article discusses the issues in Islamic Religious Education (PAI) learning at SMA Negeri 1 Kasui, Way Kanan Regency. The purpose of this study is to (1) identify the issues in Islamic Religious Education learning at SMA Negeri 1 Kasui, Way Kanan Regency; (2) identify the efforts that can be made to address these issues in Islamic Religious Education learning at SMA Negeri 1 Kasui, Way Kanan Regency. This research is a qualitative study with a descriptive qualitative approach. The population in this study consists of all students from class X 1, XI 2, and XII 3 at SMA Negeri 1 Kasui, Way Kanan Regency, in the 2021/2022 academic year, totaling 96 students. Data collection techniques in this research include observation, interviews, and documentation. The collected data were analyzed using qualitative analysis techniques with source triangulation and method triangulation. The conclusion of this study shows that the issues in Islamic Religious Education learning at SMA Negeri 1 Kasui, Way Kanan Regency, are quite varied, with various problems identified, such as: lack of motivation, monotonous teaching methods, insufficient facilities for practical classes, and lack of support from family and community environments. The researcher suggests: (1) For students, to always cultivate internal motivation to acquire beneficial knowledge and enthusiasm for learning; (2) For teachers, to provide good teaching by understanding the weaknesses and strengths of students' characters, talents, and interests, and to create a conducive learning environment with varied methods to prevent students from feeling bored or fatigued; (3) For parents, to collaborate with teachers in instilling religious education at home.